Soft bandage versus casting in the treatment of torus fracture of distal radius in children; a prospective randomized study - Thapa, Prakash Bahadur; Marasini, Rudra Prasad; Thapa, Shrawan Kumar; Pradhan, Nabeesman Singh; Giri, Shreekrishna (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Various methods of immobilization have been recommended for the treatment of torus fracture of distal radius in children. The purpose of this study is to determine if soft bandage is as effective and safe as below elbow circumferential casts in the treatment of torus fracture of the distal radius in the children. Materials & Methods: Children from 4 to 14 years of age, who presented to emergency and outpatient department of orthopaedics and trauma at National Academy of Medical Sciences with an isolated torus fracture of distal radius, were randomized and treated with either soft bandage or below-elbow plaster cast by the same investigators. Patients with associated neurovascular injuries, bilateral torus fractures, concomitant physeal injuries and associated musculoskeletal injuries were excluded. The patients were followed up at weekly interval for 4 weeks and analyzed with VAS, ROM and outcome questionnaire and data were analyzed by using SPSS 18. Results: Among the 114 patients analyzed, 57 patients were kept in soft bandage group and 57 in below-elbow cast group. The mean age in soft bandage group was 8.29 year and the mean age in below-elbow cast group was 8.55 years. There was no significant difference between the two groups with regard to patient demographics, initial fracture characteristics and mechanism of injury. Conclusion: Treatment of distal radius torus fracture with soft bandage is a cost-effective and safe in the children below 14 years of age. These minor fractures are stable and not subject to the risks of late displacement which can be very effectively treated symptomatically to provide pain relief by using soft bandage only and educating the parents about the nature of this paediatrics fracture. Journal of College of Medical Sciences-Nepal, Vol.11(4) 2015: 3-8